Modern peptide biomarkers and echocardiography in cardiac healthy haemodialysis patients - Franz Maximilian Rasche; Stephan Stoebe; Thomas Ebert; Silvana Feige; Andreas Hagendorff; Wilma Gertrud Rasche; Filip Barinka; Volker Busch; Ulrich Sack; Jochen G. Schneider; Stephan Schiekofer (BMC Nephrology, 2017)
Abstract Background In this prospective study, we aimed to assess the haemodynamic changes before and after haemodialysis (HD) in cardiac healthy subjects on chronic HD by imaging methods and endocrine markers of fluid balance. Methods Mid-regional pro-atrial natriuretic peptide (MR-proANP), N-terminal prohormone of brain natriuretic peptide (NT-proBNP), vasopressin (AVP) and copeptin (CT-proAVP), metanephrines and normetanephrines, renin and aldosterone, standard transthoracic echocardiography and diameter of vena cava inferior (VCID) were performed in 20 patients with end stage renal disease (CKD5D) before and after HD and were stratified in residual excretion (RE, less or more 0.5 l) and ultrafiltration rate (UF, less or more 2 l). Results Copeptin was significantly higher in patients before HD. Copeptin was inversely correlated with haemodialysis treatment adequacy (KT/v), RE and UF, but was not significantly influenced by age, gender and body mass index (BMI). MR-proANP was significantly reduced by haemodialysis by 27% and was inversely correlated with KT/v, but there was a significant influence by UF, RE, age, gender and BMI. NT-proBNP was significantly higher in patients before HD and was not influenced by RE and UF. Renin, aldosterone, metanephrines and normetanephrines did not demonstrate significant differences. Echocardiographic parameters and VCID were significantly correlated with RE, UF and copeptin. Conclusion Modern biomarkers will provide cardiovascular risk assessment, but elimination (UF), RE and other factors may influence the serum concentrations, e.g. in patients with renal impairment. The interpretation will be limited by altered reference ranges, and will be restricted to individual courses combined with clinical and echocardiographic data.